2009
DOI: 10.1111/j.1467-9876.2009.00692.x
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Uncertainty in Reliability Functions with Application to Aero Engine Overhaul

Abstract: We propose an approach for estimating the date of lost confidence of jet engines, which are devices with multiple components subject to disruption. A mixed Weibull distribution is estimated from a large data set subject to censoring at various times. Parametric uncertainty is derived analytically and mapped visually onto the functions of use in reliability theory, including the hazard function. We demonstrate the use of the method on a database of disruption times for components in 325 jet engines. Copyright (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A finite mixture model is used to capture the combination of individual performances. Ebden, Stranjak, and Roberts (2010) also propose a finite mixture model to describe jet engine failure modes. Here, the mixed Weibull distribution is estimated from a large data set of around 300 jet engines.…”
Section: Theory and Related Workmentioning
confidence: 99%
“…A finite mixture model is used to capture the combination of individual performances. Ebden, Stranjak, and Roberts (2010) also propose a finite mixture model to describe jet engine failure modes. Here, the mixed Weibull distribution is estimated from a large data set of around 300 jet engines.…”
Section: Theory and Related Workmentioning
confidence: 99%
“…The authors found that such model could help not only to describe the engine reliability but also to investigate the interdependent effects among the disruption modes. A finite mixture model is also used to describe jet engine failure modes in [10]. The mixed Weibull distribution is estimated from a large data set comprised of 325 jet engines.…”
Section: Introductionmentioning
confidence: 99%
“…These are the limit distributions for the maxima of exponential, heavy-tailed, and light-tailed distributions, respectively. The Weibull is that distribution typically used to estimate the distribution of component lifetimes in reliability theory [ 10 , 21 , 32 ].…”
Section: Introduction To Extreme Value Theorymentioning
confidence: 99%